THE EFFECT OF HUSBAND’S ACCOMPANYING ON REDUCING ANXIETY IN THE DELIVERY PROCESS OF PRIMIGRAVIDA MOTHERS TIME I AT PEUREULAK HEALTH CENTER EAST ACEH IN 2023: THE EFFECT OF HUSBAND’S ACCOMPANYING ON REDUCING ANXIETY IN THE DELIVERY PROCESS OF PRIMIGRAVIDA MOTHERS TIME I AT PEUREULAK HEALTH CENTER EAST ACEH IN 2023 - Simanullang, Ester; Endriani; Rumondang (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Childbirth is an important event that is eagerly awaited by every married couple. So all moral and material support is provided by the husband, family and even all members of society, for the welfare of the mother and fetus. The presence of a companion during childbirth can have a positive effect on childbirth, namely reducing morbidity, reducing pain, shortening labor, and reducing the number of deliveries by surgery, including caesarean section. Based on an initial survey conducted by researchers at the Peureulak Health Center, East Aceh, data on the number of primigravida mothers giving birth from January to April 2023 was 30 people. Among the 30 primigravida patients, interviews were conducted with 18 patients, of which 11 primigravida mothers were not accompanied by their husbands when they were about to give birth. The type of research used in this research is observational analytical research with a cross sectional approach. The location of this research was the Peureulak Health Center, East Aceh. The reason for choosing the Peureulak Health Center in East Aceh as the research site was because the number of primiparous women giving birth at the clinic was quite large. This research starts from the preparation of the thesis to the research plan from April to June 2023. The data used in this research are primary data and secondary data. This data was collected by distributing questionnaires. The majority of husbands’ assistance during the birth process of primigravida mothers in the first stage was good. The anxiety level of mothers in the first stage of labor is mostly mild anxiety. There is an influence of husband’s assistance on reducing anxiety during the first stage of labor for primigravida mothers at the Peureulak Health Center, East Aceh in 2023 with a p value <0.05. Through this research, it is hoped that health services can facilitate assistance to husbands and families during the first stage of labor and pay more attention to the anxiety of mothers in the first stage of labor.